ENHANCING OF CANDIDA TROPICALIS AND THEIR POTENTIAL ON VEGETABLE SOYBEAN CV. CHIANG MAI 84-2 GROWTH AND YIELD AS INOCULANT BIOFERTILIZER - R. D. S. Risman; K. Sungthongwises (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Since phosphorus (P) is lower in agricultural areas with acid sandy soil, it runs out in different parts of crop plants after harvesting. To boost growth and development in the next cropping system, only overuse of inorganic phosphate fertilizers can adversely affect agricultural sustainability. Phosphate-solubilizing fungi like Candida tropicalis play a role in plant P nutrition through soil P dynamics and growth hormones. Three PSF isolates (Sw01, Pu02, and Pu04) from bulk soil of fresh corn were tested for optimal media and incubation times. The results showed that Sw01 produced the highest population of 593.33×10⁸CFU L⁻¹ when cultured in TB media after five days. These PSFs were used to investigate the potential of C. tropicalis on yield components, chlorophyll pigments, and nutritional value of vegetable soybean cv. Chiang Mai 84-2. The result demonstrated that applying 50% inorganic fertilizer mixed with C. tropicalis enhanced leaf area, root length at the vegetative stage, and chlorophyll a and total chlorophyll contents at the flowering and harvest stage. This application increased pod fresh weight to 11,214 kg ha⁻¹, with an average of 28 pods plant⁻¹ and 47.50 seeds plant⁻¹ compared to fertilizer managements.